2004
DOI: 10.1007/s00330-004-2451-9
|View full text |Cite
|
Sign up to set email alerts
|

MR cystography for bladder tumor detection

Abstract: The purpose of the study was to assess the diagnostic performance of MR cystography with virtual cystoscopic and multiplanar reconstructions for detection of malignant bladder tumors. Thirty-two patients with 43 bladder tumors previously confirmed by cystoscopy (mean size 2.5 cm; 0.4-9.1 cm;) were examined at 1.5 T with a three-dimensional T2-weighted turbo spin echo sequence (TR=2911 ms, TE=500 ms, echo train length 256). Virtual cystoscopic reconstructions (VC) and multiplanar reconstructions (MPR) were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 25 publications
0
9
0
3
Order By: Relevance
“…In recent years, virtual cystoscopy (VCys) has been developed and suggested to be a promising potential alternative. It mimics the navigation environment of OCys by virtually reconstructing the whole bladder in three-dimensional (3D) space [9]-[13]. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, virtual cystoscopy (VCys) has been developed and suggested to be a promising potential alternative. It mimics the navigation environment of OCys by virtually reconstructing the whole bladder in three-dimensional (3D) space [9]-[13]. …”
Section: Introductionmentioning
confidence: 99%
“…Most previous MR cystography studies [3], [7], [9-11] found that T 1 –/T 2 – rather than PD–weighted scanning protocol is in favored for assessing the anatomical structures or pathologies in the urinary bladder. Compared with T 2 –weighed MR imaging, T 1 –weighted imaging enhances the desired signals or the bladder wall by lowering the lumen intensity as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance (MR) cystography is a very promising, completely non-invasive procedure for detection and management of bladder lesions [3]–[5]. Since carcinoma tumors at early stages of penetration can be as small as less than 5mm [6], images with high spatial resolution and sufficient signal–to–noise ratio (SNR) are required to present the bladder wall, where bladder lesions reside.…”
Section: Introductionmentioning
confidence: 99%
“…Lammle et al [29] reported detection rates of 90.9% and 100% for all tumors and for tumors greater than 1cm, respectively in 24 BCa patients. Beer et al [30] reported sensitivity and specificity of 91% for MRC in 32 patients with 43 lesions. MRC has several advantages over conventional cystoscopy such as being relatively impervious to hematuria, urethral strictures and anterior bladder wall lesions (which can be difficult to reach via cystoscopy), however, its limitations include a time consuming costly procedure requiring expertise which has difficulty detecting of flat lesions.…”
Section: Mrimentioning
confidence: 99%